Taxation of civil aviation fuels as a source of financing for vulnerable countries - Alou Adessé Dama; Vianney Dequiedt; Audrey-Anne de Ubeda; Grégoire Rota-Graziosi (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
Lifting the tax exemption for jet fuel used for international flights is a recurring demand from many stakeholders committed to sustainable development. Currently, this exemption keeps the carbon pricing of jet fuel at an excessively low level and is inconsistent with the decarbonisation objectives set by the international community. A tax of exteuro0.33 per litre would raise exteuro18 billion per year, while a tax of exteuro0.1 per litre would raise exteuro5.8 billion per year. This tax would ultimately be based on a polluter-pays principle and the concentrated structure of the sector should facilitate its collection. While international negotiations are essential for adoption worldwide, the introduction of such a tax, or at least the end of the current tax exemption, does not contradict the Chicago Convention, which has laid the foundations for international cooperation in civil aviation since 1944. Although it alone cannot finance the climate change adaptation needs of countries in the South, the taxation of civil aviation fuels is an interesting avenue for short-term funding for vulnerable countries. In the longer term, such taxation would accelerate the low-carbon transition of the international civil aviation sector.
Keywords: 330; Taxation; Kerosene; Civil aviation; Loss and damage funds; Financing for vulnerable countries